Contrast-induced acute kidney injury. Issue 2 (March 2015) - Briguori, Carlo; Donnarumma, Elvira; Quintavalle, Cristina; Fiore, Danilo; Condorelli, Gerolama
<x xml:space="preserve">Abstract</x> Purpose of review Contrast-induced acute kidney injury (CI-AKI) is an impairment of renal function following contrast media administration in the absence of an alternative cause. It represents a powerful predictor of poor early and late outcomes. Here, we review the major strategies to prevent CI-AKI. Recent findings Hydration represents the gold standard as a prophylactic measure to prevent CI-AKI, acting by increasing urine flow rate and, thereby, by limiting the time of contact between the contrast media and the tubular epithelial cells. An optimal hydration regimen should be defined according to predefined clinical markers, such as urine flow rate, or left ventricular end-diastolic pressure. Recently, high-dose statins pretreatment has been included in the guidelines of CI-AKI prevention. However, uncertainty still exists on the efficacy of several compounds tested in both observational trials and randomized studies to prevent CI-AKI. Compounds evaluated include diuretics (furosemide), antioxidants (i.e. N-acetylcysteine and statins) and vasodilators (i.e. calcium antagonists, dopamine and fenoldopam). Summary Hydration still represents the most reliable strategy to prevent CI-AKI. New prophylactic strategies for acute kidney injury are still under investigation.